Application of a health technology assessment framework to digital health technologies that manage chronic disease: a systematic review. (20th December 2022) - von Huben, Amy; Howell, Martin; Carrello, Joseph; Norris, Sarah; Wortley, Sally; Ritchie, Angus; Howard, Kirsten
Abstract: Background: As health services increasingly make investment decisions in digital health technologies (DHTs), a DHT-specific and comprehensive health technology assessment (HTA) process is crucial in assessing value-for-money. Research in DHTs is ever-increasing, but whether it covers the content required for HTA is unknown. Objectives: To summarize current trends in primary research on DHTs that manage chronic disease at home, particularly the coverage of content recommended for DHT-specific and comprehensive HTA. Methods: Medline, Embase, Econlit, CINAHL, and The Cochrane Library (1 January 2015 to 20 March 2020) were searched for primary research studies using keywords related to DHT and HTA domains. Studies were assessed for coverage of the most frequently recommended content to be considered in a nine domain DHT-specific HTA previously developed. Results: A total of 178 DHT interventions were identified, predominantly randomized controlled trials targeting cardiovascular disease/diabetes in high- to middle-income countries. A coverage assessment of the cardiovascular and diabetes DHT studies (112) revealed less than half covered DHT-specific content in all but the health problem domain. Content common to all technologies but essential for DHTs was covered by more than half the studies in all domains except for the effectiveness and ethical analysis domains. Conclusions: Although DHT research is increasing, it is not covering all the content recommended for a DHT-specific and comprehensive HTA. The inability to conduct such an HTA may lead to health services making suboptimal investment decisions. Measures to increase the quality of trial design and reporting are required in DHT primary research.